Letter : Basque Boys Training Committee - Willis, Robert
1939-07-11 038-0082-001 BASQUE CHILDREN'S COMMITTEE CHAIRMAN: THE DUCHESS OF ATHOLL, D.B.E., D.C.L. VICE-CHAIRMEN: MISS ELEANOR RATHBONE, M.P. H.V. TEWSON, ESQ. HON. SECRETARIES: Mr. WILFRID ROBERTS, M.P. LT.-COL. J.R.J. MACNAMARA, M.P. Mr. D.R. GRENFELL, M.P. HON. TREASURER: VISCOUNT CECIL OF CHELWOOD, P.C. K.C. ORGANISING SECRETARY: DR. BETTY MORGAN. 30, ECCLESTON STREET, LONDON, S.W.1. TELEPHONE: SLOANE 9866 BASQUE BOYS TRAINING COMMITTEE 11th. July, 1939 Dear Sir, I enclose a short statement of the work that is being done by the Basque Boys Training Committee for the older Basque boys in England, and we should be grateful if you would be good enough to read this letter at your Conference and give permission for copies of the statement to be distributed. We have in our charge about one hundred and fifty boys between the ages of 14-18, who may never be able to return to Spain because they are orphans or because of the political position of their parents, and our Committee has undertaken the responsibility of maintaining them until they are in a position to support themselves. The Home Office allows them to be placed in work provided in every case that there is no displacement of British labour, and that the conditions of their employment are not less favourable than those that would be accorded to British employees in the trade in the district concerned. Under these conditions, and with the help of Trade Union Committees and sympathetic persons and organisations, work has already been found for a number of them in agriculture and industry. But we still have a hundred or more to place, and we ask for the special co-operation of the Trade Union Movement not only in assisting us to find suitable openings, but also in protecting their interests and undertaking to see that Trade Union conditions are rigorously observed when they have been placed in work. The cost of maintaining these boys in England until they able to support themselves will necessarily be extremely heavy, and if the work that we are beginning now is to be carried through we must have the fullest support and co-opera- 292/946/38/82(I)